2018
DOI: 10.1016/j.ajpath.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Flap Endonuclease 1 Correlates with Enhanced Proliferation and Poor Prognosis of Non–Small-Cell Lung Cancer

Abstract: Flap endonuclease 1 (FEN1) plays a crucial role in both DNA replication and damage repair. In this study, FEN1 expression and its clinical-pathologic significance in non-small-cell lung cancer (NSCLC) was investigated. Quantitative RT-PCR and immunohistochemistry analysis identified that both FEN1 mRNA and protein were highly overexpressed in about 36% of 136 cancer tissues compared to adjacent tissues, in which FEN1 was generally undetectable. Notably, patients with FEN1-overexpressed cancers were prone to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 39 publications
5
67
0
Order By: Relevance
“…He et al (2017) found that FEN1 plays a key role in the rapid proliferation of NSCLC cells and confirmed in a mouse model that treatment with an FEN1 inhibitor enhanced the sensitivity of NSCLC cells to DNA damaging agents and that combined therapy with cisplatin could significantly inhibit the progression of cancer cells. Using quantitative RT-PCR and immunohistochemical analysis, Zhang et al (2018) revealed that FEN1 is highly overexpressed in NSCLC tissues and that the higher the expression of FEN1 is, the poorer the tumor differentiation and prognosis. In vitro experiments also confirmed that the downregulation of FEN1 could lead to G1/S or G2/M cell cycle arrest in NSCLC cells and inhibit cell proliferation in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2017) found that FEN1 plays a key role in the rapid proliferation of NSCLC cells and confirmed in a mouse model that treatment with an FEN1 inhibitor enhanced the sensitivity of NSCLC cells to DNA damaging agents and that combined therapy with cisplatin could significantly inhibit the progression of cancer cells. Using quantitative RT-PCR and immunohistochemical analysis, Zhang et al (2018) revealed that FEN1 is highly overexpressed in NSCLC tissues and that the higher the expression of FEN1 is, the poorer the tumor differentiation and prognosis. In vitro experiments also confirmed that the downregulation of FEN1 could lead to G1/S or G2/M cell cycle arrest in NSCLC cells and inhibit cell proliferation in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…26 Overexpression of FEN1 has been associated with enhanced cancer cell proliferation or poor clinical outcome in gastric, 27 breast, 28 ovarian 28 and non-small-cell lung cancer. 29 FEN1 is known to be activated by PCNA 30 and RFC, 31 Figure 3B,C). It is plausible that HNRNPLL may drive this coordinated machinery for lagging strand synthesis by upregulating these components.…”
Section: Hnrnpll-medium/low (N = 360)mentioning
confidence: 99%
“…On the other hand, FEN1 is a multifunctional structure-specific nuclease that has a critical role in maintaining human genome stability. Overexpression of this gene correlates with enhanced proliferation and poor prognosis of lung cancer [44]. The exact underlying mechanism through which CHEK1 modulates cancer progression needs to be further investigated.…”
Section: Co-expression Profile Of Chek1 In Colorectal Cancermentioning
confidence: 99%
“…The exact underlying mechanism through which CHEK1 modulates cancer progression needs to be further investigated. poor prognosis of lung cancer [44]. The exact underlying mechanism through which CHEK1 modulates cancer progression needs to be further investigated.…”
Section: Co-expression Profile Of Chek1 In Colorectal Cancermentioning
confidence: 99%